Literature review: Economic value of utilization of crab shell waste (Case study of PT. Toba Surimi Industri in Tanjungpinang City, Riau Island Province) - Mardiana E Fachry; Alpiani Alpiani (Sekolah Tinggi Ilmu Pertanian Wuna, 2021)
Writing this scientific paper aims to determine the economic value of the potential waste of crab shells produced by PT. Toba Surimi Industry in Tanjungpinang City, Riau Islands Province. The company has not utilized crab shell waste. In contrast, crab shell waste can provide economic value that provides a lot of additional value. Crab shell waste can be processed into chitosan, which has many functions in various sectors, both in the fisheries, automotive and health industries, and other sectors. Chitosan is produced from the chitin substance contained in crab shells through deproteination, demineralization, and deacetylation. The economic value that can generate from the utilization of crab shell waste PT. Toba Surimi Industry when processed into chitosan with a crab shell weight of 270 kg/day, which is Rp. 40.500.000/day.